The prevalence and predictors of mental health diagnoses and suicide among U.S. college students: Implications for addressing disparities in service use - Liu, Cindy H.; Stevens, Courtney; Wong, Sylvia H.M.; Yasui, Miwa; Chen, Justin A. (Depression and anxiety, 2019)
Background The college years represent a period of increased vulnerability for a wide range of mental health (MH) challenges. The onset of common psychiatric conditions occurs during this period of development. Increases in depression, anxiety, and suicidality among U.S. college students have been observed. This study identified prevalence and correlates of MH diagnoses and suicidality in a recent sample of U.S. college students. Methods The Spring 2015 American College Health Association‐National College Health Assessment (ACHA‐NCHA) survey assessed MH diagnoses and suicidality from U.S. undergraduate students (n = 67,308) across 108 institutions. Results Stress was strongly associated with a greater likelihood of suicide attempts and MH diagnoses, even among students reporting 1–2 stressful events (OR [odds ratio] range 1.6–2.6, CI [confidence interval] = 1.2–3.2). Bisexual students were more likely to report MH diagnoses and suicidality, compared to heterosexual and gay/lesbian students (OR range 1.5–3.9, CI = 1.8–4.3), with over half engaging in suicidal ideation and self‐harm, and over a quarter reporting suicide attempts. Transgender students reported a higher rate of MH diagnoses and suicidality relative to females (OR range 1.9–2.4, CI = 1.1–3.4). Racial/ethnic minority students were generally less likely to report MH diagnoses relative to Whites, although the likelihood for suicidality was mixed. Conclusions The high rate of multiple stress exposures among the U.S. college population and the high impacts of stress on MH and suicidality point to an urgent need for service utilization strategies, especially among racial/ethnic, sexual, or gender minorities. Campuses must consider student experiences to mitigate stress during this developmental period.